A construção da representação feminina na CPI da pandemia pela perspectiva da análise do discurso ecossistêmica - Prado, Juliana Batista do (2023)
Based on a perspective of the EIC (COUTO, 2013a), this study proposes to analyze discursively - from the perspective of the natural, mental, and social language ecosystems - the construction of female representation in relation to three women (doctors) questioned in the sessions of the Parliamentary Commission of Inquiry (CPI) of the Pandemic in 2021.Strategies were used to interrogate in order to defend or attack and present the objectives and viewpoints regarding the healthcare professionals. Given the magnitude of the event, the focus was on the performance of the doctors in this corpus, in the face of the attacks suffered, as representations of battles to survive discursively and, at the same time, as a source of entertainment for the viewers (especially on the internet). The methodology adopts a qualitative and multimethodological (ecometodology) approach, with interpretation based on the guidelines of Ecosystemic Linguistics and its intersections with areas such as Ecosystemic Discourse Analysis (which advocates for the ideology of life and ecological values, prioritizing the self-realization of beings). The interrelationship between linguistic and social meanings will be evaluated through the use of recorded video excerpts from the CPI sessions, stenographic records from the Federal Senate, and news articles disseminated through various online newspapers, social media, and the official website of the Federal Senate. Authors such as Couto (2016), Couto et al. (2015), Couto and Fernandes (2021), among others, form the theoretical foundation of this work, providing concepts and discussions that align with the research objectives.